Conjunction According To Al-Sirafi From The Perspective of Contextual Theory (Journal of the College of Basic Education, 2026)
Given the importance of Sibawayh's book, which is the first book on Arabic sciences to reach us, and considering the importance of ancient texts, Given the need to reread it from a modern perspective, this attempt at a contextual study of the most important commentary on Sibawayh's book, namely al-Sirafi's commentary on Sibawayh's work, presents this study. The idea behind this study is to examine al-Sirafi's use of conjunction from the perspective of modern contextual studies. We found that this text was not analyzed, nor was it studied as an ancient grammatical text according to the principles of modern contextual studies. Therefore, the most important aspects of this study came in talking about conjunction and conjunction letters and their effect on the text from the perspective of the context and the most important texts that came from Al-Sirafi in which he talks about the role of conjunction in directing the context.